2019
DOI: 10.1136/jclinpath-2019-205769
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations and expression of PTEN and its relationship with cancer stem cell markers to investigate pathogenesis and to evaluate prognosis in hepatocellular carcinoma

Abstract: AimsTo investigate molecular alteration and expression of phosphatase and tensin homolog deleted on chromosome 10 (PTEN) gene in hepatocellular carcinoma (HCC), and to evaluate the correlation between PTEN and cancer stem cell (CSC) markers and the prognostic value of these markers.MethodsWe evaluated changes of PTEN and CSC markers (CD133, epithelial cell adhesion molecule (EpCAM) and CK19) in 183 resecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 26 publications
2
16
0
Order By: Relevance
“…At the initial stage of our investigation, it was found that PTEN was expressed at low levels in HCC tissues and cell lines and it was in association with shorter overall survival of patients, staging and metastasis. PTEN has been reported to be downregulated in nearly half of the cases of HCC tissues while reduction of PTEN expression is identified as an independent biomarker for the recurrence and overall survival of HCC as it leads to reduced recurrence-free survival and overall survival of patients [17]. Concordant with our results, PTEN has been proposed as a promising biomarker of the tumor grade and disease stage in patients with HCC considering its role in counterbalancing apoptosis and proliferation [18].…”
Section: Discussionsupporting
confidence: 87%
“…At the initial stage of our investigation, it was found that PTEN was expressed at low levels in HCC tissues and cell lines and it was in association with shorter overall survival of patients, staging and metastasis. PTEN has been reported to be downregulated in nearly half of the cases of HCC tissues while reduction of PTEN expression is identified as an independent biomarker for the recurrence and overall survival of HCC as it leads to reduced recurrence-free survival and overall survival of patients [17]. Concordant with our results, PTEN has been proposed as a promising biomarker of the tumor grade and disease stage in patients with HCC considering its role in counterbalancing apoptosis and proliferation [18].…”
Section: Discussionsupporting
confidence: 87%
“…In the validation phase, GNAS, MSH2, and survivin displayed better diagnostic performances than other TAAs, while PTEN was not a good performer, which was consistent with previous verification results, and may have been caused by the reduction of PTEN expression in HCC tissue [49,50]. Although autoantibodies against PAX5 and GNA11 showed little difference between the HCC and NC groups in the process of univariate analysis in the validation dataset, they were still selected as statistically significant predictors (risk factors) for HCC in multivariate analysis by logistic regression in the training dataset.…”
Section: Discussionsupporting
confidence: 88%
“…Reportedly, the inactivation of PTEN, which is known to suppress PI3K, was associated with the expression of PD-L1 in glioma [37]. More importantly, a recent report suggested that inactivating the mutation of PTEN and activating that of PI3K were associated with the expression of CK19 in HCC [38], where PD-L1 expression was frequent. In addition, the activation of the PI3K-Akt pathway is one of the characteristics of CSCs [39].…”
Section: Discussionmentioning
confidence: 99%